2015
DOI: 10.1074/jbc.m115.659672
|View full text |Cite
|
Sign up to set email alerts
|

Channel Gating Dependence on Pore Lining Helix Glycine Residues in Skeletal Muscle Ryanodine Receptor

Abstract: Type 1 ryanodine receptors (RyR1s) release Ca(2+) from the sarcoplasmic reticulum to initiate skeletal muscle contraction. The role of RyR1-G4934 and -G4941 in the pore-lining helix in channel gating and ion permeation was probed by replacing them with amino acid residues of increasing side chain volume. RyR1-G4934A, -G4941A, and -G4941V mutant channels exhibited a caffeine-induced Ca(2+) release response in HEK293 cells and bound the RyR-specific ligand [(3)H]ryanodine. In single channel recordings, significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Although the radial tilting angle and the twisting angle of the S6 helix are accurately reproduced in our model, we note a difference in the lateral tilting angle for the S6 helix ( In our open-channel model, the direction of rotation brings Ile-4937 past Gly-4934. We previously showed that the G4934A mutation reduced the Ca 2ϩ current, whereas the G4934V mutation resulted in loss of function of purified channels (31). In the current study, we find that RyR1-G4934V can form functional channels with reduced Ca 2ϩ current, when avoiding detergent exposure throughout the process of purification.…”
Section: Conformational Changes Of Ryr1 Channel Openingsupporting
confidence: 63%
See 1 more Smart Citation
“…Although the radial tilting angle and the twisting angle of the S6 helix are accurately reproduced in our model, we note a difference in the lateral tilting angle for the S6 helix ( In our open-channel model, the direction of rotation brings Ile-4937 past Gly-4934. We previously showed that the G4934A mutation reduced the Ca 2ϩ current, whereas the G4934V mutation resulted in loss of function of purified channels (31). In the current study, we find that RyR1-G4934V can form functional channels with reduced Ca 2ϩ current, when avoiding detergent exposure throughout the process of purification.…”
Section: Conformational Changes Of Ryr1 Channel Openingsupporting
confidence: 63%
“…We previously investigated the single channel properties of purified RyR1-G4934A and RyR1-G4934V mutants (31). We here examine the single channel properties of these mutants in membrane fractions avoiding exposure to detergent during purification of RyR1s.…”
Section: Altering Open-channel Contacts In the S6 Helix Affects Channmentioning
confidence: 99%
“…Dilation of the pore does not occur via bending of S6 at a single ‘hinge’ alone, but rather by bowing and distortion of the S6 helix from a point midway through the membrane (Figure 4B), near the position of G4934 hinge, previously identified to influence gating of both RyR1 and RyR2 (Euden et al, 2013; Mei et al, 2015). Three other notable changes occur in the transmembrane region coincident with pore dilation.…”
Section: Resultsmentioning
confidence: 84%
“…Single-channel studies were done using purified RyR2 channel preparations. We reported that replacement of RyR1-Gly-4934 and Gly-4941 with Ala altered RyR1 channel function in single-channel measurements using purified RyR1 preparations (15). A mutation further increasing the side-chain volume at Gly-4934 (G4934V) resulted in loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis and single-channel measurements showed that negatively charged luminal residues Asp-4899 and Glu-4900 and the cytosolic residues Asp-4938, Glu-4942, and Asp-4945 in the pore-lining S6 helix impact RyR1 ion permeation and selectivity (13,14). The RyR1 S6 pore-lining helix has also two conserved glycines, Gly-4934 and Gly-4941, whose replacement with uncharged residues with an increased sidechain volume altered RyR1 channel gating and ion permeation (15). High-resolution cryoelectron microscopy (cryo-EM) using open RyR1 ( Fig.…”
mentioning
confidence: 99%